2023
DOI: 10.3390/s23136057
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Optimal Predictors and Sampling Frequency to Develop Nutrient Soft Sensors Using Random Forest

Muhammad Arhab,
Jingshui Huang

Abstract: Despite advancements in sensor technology, monitoring nutrients in situ and in real-time is still challenging and expensive. Soft sensors, based on data-driven models, offer an alternative to direct nutrient measurements. However, the high demand for data required for their development poses logistical issues with data handling. To address this, the study aimed to determine the optimal subset of predictors and the sampling frequency for developing nutrient soft sensors using random forest. The study used water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Regarding forecasting, in various scientific fields (e.g., climatology, hydrology, and landslide risk management), it has been found that forecasts benefit from high frequency data (e.g., Arhab & Huang, 2023;Bozzano et al, 2018;Leyton & Fritsch, 2004;Liu & Han, 2013). However, in ecology the few studies that investigated how forecasting is affected by sampling frequency found that sampling more often could both improve and worsen forecasts (Derot et al, 2020;Wauchope et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding forecasting, in various scientific fields (e.g., climatology, hydrology, and landslide risk management), it has been found that forecasts benefit from high frequency data (e.g., Arhab & Huang, 2023;Bozzano et al, 2018;Leyton & Fritsch, 2004;Liu & Han, 2013). However, in ecology the few studies that investigated how forecasting is affected by sampling frequency found that sampling more often could both improve and worsen forecasts (Derot et al, 2020;Wauchope et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…climatology, hydrology, landslide risk management), it has been found that they benefit from high frequency data (e.g. Liu and Han 2013;Leyton and Fritsch 2004;Bozzano, Mazzanti, and Moretto 2018;Arhab and Huang 2023).…”
Section: Introductionmentioning
confidence: 99%
“…climatology, hydrology, landslide risk management), it has been found that they benefit from high frequency data (e.g. Liu and Han 2013; Leyton and Fritsch 2004; Bozzano, Mazzanti, and Moretto 2018; Arhab and Huang 2023). However, in ecology the few studies that investigated how forecasting is affected by sampling frequency found that sampling more often could both improve and worsen forecasts (Wauchope et al 2019; Derot, Yajima, and Schmitt 2020).…”
Section: Introductionmentioning
confidence: 99%